1987
DOI: 10.1007/bf02773819
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic portal-systemic shunt: Its etiology and diagnosis

Abstract: Four cases of enormous shunt between portal and hepatic veins (portal-hepatic venous shunt) are reported with special reference to sonographic and portographic findings. Ultrasonography, an examination for screening, delineated a snail-like anechoic area in the liver, its connection with the portal and hepatic veins, and marked dilatation of the veins connecting with the shunt. Transarterial or percutaneous transhepatic portography, a method for definitive diagnosis, demonstrated large pooling of the contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Another case was reported of a newborn with a shunt with spontaneous resolve in first year of age (8,13). SIPSVS may be demonstrated in any age of life between 20-day-old and late seventies (3,5,12,14,18,19,20,22,24,26,31). Wide range distribution in case reports may make us speculate role of different mechanism in development of SIPSVS.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another case was reported of a newborn with a shunt with spontaneous resolve in first year of age (8,13). SIPSVS may be demonstrated in any age of life between 20-day-old and late seventies (3,5,12,14,18,19,20,22,24,26,31). Wide range distribution in case reports may make us speculate role of different mechanism in development of SIPSVS.…”
Section: Discussionmentioning
confidence: 94%
“…The late hyperinsulinism then leads to secondary hypoglycemia. These cases may benefit dietetic treatment (7,9,12,18).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-and extrahepatic venous anomalies mediating portosystemic shunting have been described in at least 24 patients [2,4,11,13,20,21,22,25,26,32] and in one dog [16]. In 11 of the patients, and in the dog, encephalopathy developed, in 5 of the patients decades before the venous anomaly was diagnosed [4,13,22,25].…”
Section: Discussionmentioning
confidence: 97%
“…Extrahepatic hepatofugal shunts are well-visualized radiol0gi-cally, whereas microscopic intrahepatic shunts are beyond the resolution of an imaging test. Macroscopic IPHVS were rarely detected before the widespread use of US and CT. Horiguchi et al [4] reported only two cases [10,11] before the introduction of these diagnostic modalities, while six cases, including those of their own, were reported within 2 years after their use. Likely etiologies of these macroscopic shunts include congenital [101, rupture of portal venous aneurysm [12,13], patent or reopening of ductus venosus [1] in a cirrhotic patient, and acquired vascular disorder as a sequela to parenchymaI collapse from hepatitis [11].…”
Section: Casementioning
confidence: 99%
“…Summary of five patients with macroscopic IPHVS raphy (US) and computed tomography (CT), a rare entity of intrahepatic direct communication between a portal venous branch and the hepatic vein [macroscopic intrahepatic portal-hepatic venous shunt (IPHVS)] has been sporadically reported [1][2][3][4][5]. Magnetic resonance imaging (MRI) findings of this entity, however, have not been reported.…”
mentioning
confidence: 99%